Welcome home, Mouse - Kleven, Elisa (Berkeley : Tricycle Press, 2010)
Stanley the elephant, who's very clumsy, accidentally smashes Mouse's house, then promises to try to make a new one.
2-5.
Baby-K.
Keywords: Dwellings -- Design and construction -- Juvenile fiction; Clumsiness in children -- Juvenile fiction; Elephants -- Juvenile fiction; Mice -- Juvenile fiction; Dwellings -- Design and construction -- Fiction; Clumsiness -- Fiction; Elephants -- Fiction; Mice -- Fiction